SKELETAL MINERALOGY OF BRYOZOANS: TAXONOMIC AND TEMPORAL PATTERNS - Smith A.M.; Key Jr.M.M.; Gordon D.P. (My University, 2006)
Skeletal carbonate mineralogy of 1183 specimens of marine bryozoans from the literature was examined for phylogenetic patterns in order to elucidate the effects of bryozoan mineralogy on geochemical and paleoenvironmental analysis. Colonies are composed of calcite (66% of specimens), aragonite (17% of specimens) or various mixtures of the two (17% specimens) (phylum mean = 72.9 wt.% calcite, n = 1051). When calcite is present, it ranges from 0.0 to 13.7 wt.% MgCO3 (mean = 5.0 wt.% MgCO3, n = 873). Most (61%) calcitic specimens are formed of intermediate-Mg calcite (4 to 8 wt.% MgCO3), others (28%) of low-Mg calcite (0 to 4 wt.% MgCO3), and few of high-Mg calcite (> 8 wt.% MgCO3). The phylum occupies at least 63% of the theoretical mineralogical "space" available to biomineralisation. Most of this variation occurs in the class Gymnolaemata, order Cheilostomata, suborder Neocheilostomata. Fossil and Recent stenolaemate taxa are generally low- to intermediate-Mg calcite (mean = 99.7 wt.% calcite, 2.6 wt.% MgCO3, 17% of available biomineral space). Variability among families is related in a general way to first appearance datum: families younger than 100 Ma display greater mineralogical complexity than older ones. The cheilostome infraorder Flustrina includes unusual free-living aragonitic families, dual-calcite skeletons (mainly low-Mg calcite, but with secondary high-Mg calcite), and some genera with considerable mineralogical variability. Families (e.g., Membraniporidae and Phidoloporidae) and species (e.g., Schizoporella unicornis) with the highest degree of variability have potential for environmental correlations with mineralogy, paleoenvironmental interpretation, and possibly molecular investigation for potential cryptic species. Stenolaemate families, genera and species with low variability, on the other hand, are well-suited for geochemical work such as stable isotope analysis. Variability in the skeletal mineralogy of bryozoans suggests that they may be useful in geochemical, phylogenetic, and paleoenvironmental studies, with careful choice of study material. © 2006 Elsevier B.V. All rights reserved.
Keywords: ARAGONITE; BIOMINERALIZATION; BRYOZOANS; CALCITE; CARBONATE MINERALOGY